2012
DOI: 10.1186/1756-0500-5-312
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity reduces risk for colon polyps in a multiethnic colorectal cancer screening population

Abstract: BackgroundIdentifying modifiable factors that influence the epidemiology of colorectal cancer incidence among multiethnic groups might be informative for the development of public health strategies targeting the disease. Minimal data exists describing the impact of physical activity on colorectal polyp risk in United States minority populations. The aim of this study is to evaluate the relationship of exercise on the prevalence of polyps in a multiethnic colorectal cancer screening population.ResultsWe enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 30 publications
0
42
0
1
Order By: Relevance
“…In one of the earliest reports to examine polyp prevalence by race, Lieberman and colleagues (10) found that blacks had a higher risk of larger polyps (> 9mm) compared to whites, especially African-American women. Lebwohl and colleagues (5) found an increased risk among blacks compared to whites of proximal and advanced neoplasm but also reported an association with any adenoma (OR 1.76 (95% CI 1.52–2.04)) findings which were recently corroborated by Sanchez et al (RR 3.0 (95% CI 1.1–8.3))(7). Others(8, 9), however, have observed a similar risk of prevalent and advanced adenomas by race, but a higher risk of proximal adenomas in blacks compared to whites – proximal location is associated with poorer survival among patients with invasive cancer (3133).…”
Section: Discussionmentioning
confidence: 70%
“…In one of the earliest reports to examine polyp prevalence by race, Lieberman and colleagues (10) found that blacks had a higher risk of larger polyps (> 9mm) compared to whites, especially African-American women. Lebwohl and colleagues (5) found an increased risk among blacks compared to whites of proximal and advanced neoplasm but also reported an association with any adenoma (OR 1.76 (95% CI 1.52–2.04)) findings which were recently corroborated by Sanchez et al (RR 3.0 (95% CI 1.1–8.3))(7). Others(8, 9), however, have observed a similar risk of prevalent and advanced adenomas by race, but a higher risk of proximal adenomas in blacks compared to whites – proximal location is associated with poorer survival among patients with invasive cancer (3133).…”
Section: Discussionmentioning
confidence: 70%
“…Colon polyp is a common digestive system disease, with a high clinical detection rate (9,10). Colorectal polyps are pathologically classified as neoplastic or nonneoplastic polyps (11).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who reported exercising one or more hours weekly were regarded as "physically active" [16].…”
Section: Study Populationmentioning
confidence: 99%